Penggunaan Single Sign On (SSO) pada Jaringan Internet Badan Pengkajian dan Penerapan Teknologi (BPPT) - Johan Muliadi Kerta; Panji Adiprabowo; Eva Kusmiyati; Sylvia Astri Wulandari Rahardjo (Bina Nusantara University, 2011)
Using various applications needs more than one authentication or user and password to login. Users in BPPT found this problem on their network application. Implementation of Single Sign On can help users to use only one authentication for many applications. Therefore a research is conducted to design and implement Single Sign On system that simplify and facilitate the user's email account to access application. Data are collected from literature study, system observation, and interviews while the design uses Network Development Life Cycle (NDLC) method. The research results in a Single Sign On system that utilizez Lightweight Directory Access Protocol (LDAP). In addition, Remote Authentication Dial-In User Service (RADIUS) is managed in accordance with the needs of the institution. Single Sign On system designed runs well and is able to provide conveniences for the user to use the services of existing applications, as it provides a standard email address to the user's identity. It also helps administrators to perform control of users trying to login.